The Interplay of Ambidextrous Intellectual Capital and Ambidexterity: Achieving Sustainable Performance in Technological Turbulent Environments - Imran, Dr. Muhammad; Mahmood , Dr. Tarique; Ali , Dr. Liaqat; Khan , Dr. Afaq Ali (Al-Qanṭara, 2025)
Purpose- This research will seek to examine the effects of intellectual capital (including human, structural, and relational capital) and sustainable firm performance. It also examines how the ambidextrous organization mediates this relationship as well as the moderating effects of technological turbulence in this relationship. Design/Methodology- The research design was a cross-sectional quantitative research. The information was gathered through structured survey to managers and employees in manufacturing industries. Partial least squares structural equation modeling (PLS-SEM) was used to test the hypotheses proposed. Findings- The results verify the fact that the three aspects of intellectual capital positively affect the sustainable performance. The organization is able to balance between exploration and exploitation (ambidexterity), which is where this relationship is completely mediated. Also, technological turbulence enhances the calibrating impact of the ambidextrous organization on sustainable performance. Practical Implications - To succeed in the turbulent markets, the practitioners need to invest strategically in the development of all aspects of intellectual capital. Moreover, designing an organizational culture that is both innovation-oriented and productive would be a key to transforming intellectual resources into actual and long-term results. Managerial implications - The managers are encouraged to incorporate the intellectual capital measures in their performance management systems and strategic planning. Leadership should be the frontier of ambidextrous practices, which allocate resources towards exploration innovation and operational efficiency to ensure that they get maximum value out of their human, structural and relational capital. Originality/value - This paper presents a new integrative model whereby the ambidextrous organization is placed as a point of convergence between intellectual capital and sustainable performance. It is the only source that does not view technological turbulence as a preventive factor, but as a situational enhancer of the returns of ambidextrous capabilities